IMPLEMENTASI TROPICAL FOREST CONSERVATION ACTION SUMATERA (TFCA-S) DALAM KONSERVASI HUTAN RIAU (2017-2020) - Bayta Nur Afni; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This research was motivated by deforestation in Indonesia and was carried out by analyzing the implementation of the TFCA-S program. This Program created by the United States and Indonesia, as an effort to conserve tropical forests with the Debt for Nature Swap funding mechanism model in Sumatra, especially Riau. One of the Debt for Nature Swap programs in Indonesia is TFCA-Sumatera. The use of the Debt for Nature Swap funding mechanism is considered as an alternative for developing countries. The conceptual famework of this research is to use the theory of Foreign Assistance and the Debt for Nature Swap concept. The research method used is a qualitative research method, where data collection was through interviews and literature studies. The conclusions from this research where the TFCA-Sumatra program initiated by the United States and Indonesia can be an alternative effort to preserve Indonesia's forests and biodiversity (in this case especially Riau), and also extensive from the threat of deforestation, extinction of wildlife, and climate change. local, regional and global climate. Keywords: Implementation, Forest Conservation, TFCA-S Program, Debt for Nature Swap